The syntax and semantics of infinitives of result in English - Whelpton, M; Whelpton, M. J. (1995)
﻿ This thesis concerns infinitives of result in English, examples of which are given under (a-c). (a) John designed a battery to operate at high temperatures. (b) John designed a battery to win a prize. (c) John designed a battery for the competition, only to discover that he was ineligible. The infinitive in (a) is called a Purpose Clause; the infinitive in (b) is called a Rationale Clause; and the infinitive in (c) is called a Telic Clause. These infinitives are optional modifiers of the verbs with which they occur. I argue, however, that important characteristics of their form and interpretation follow naturally if the infinitives are assumed to have argument structures which must be incorporated into the argument structure of the verb they modify. In Chapter 1, I introduce the constructions and offer a general discussion of the problems posed by modifiers in a study of natural language semantics, arguing that these problems are best addressed by viewing modifiers as predicates of a standard sort. This establishes a central hypothesis of this thesis, namely that the syntax and semantics of modification should be incorporated into the theory of argument structure, or "theta theory". In Chapter 2, I offer a summary of key works in the literature in two areas: theories of argument projection by Williams and Higginbotham and studies of infinitives of result by Faraci, Bach, Chierchia, and Jones. In Chapter 3, I apply a range of syntactic tests to establish the structural relation of the infinitives to the sentences they modify. I argue that the infinitives are embedded at an increasing distance from the modified verb, from which important characteristics of their distribution follow. In Chapter 4, I turn to the internal syntax of the constructions and consider the nature and distribution of the gaps that occur within each infinitive and the manner in which those gaps are interpreted. I relate key characteristics of the infinitives to the nature of their argument grids. I also address constraints on interpretation introduced by pronominal binding in the infinitives. In Chapter 5, I discuss a variety of problems on the syntax-semantics interface involving argument structure and control. The issues raised move from the relatively syntactic (phrase structure accounts of Purpose Clause antecedence and the possibility of event control for the Rationale and Telic Clauses) to the philosophical semantic (causal efficacy and the nature of resultant states in the interpretation of the Purpose Clause). I then offer a full sample analysis of a sentence modified by all three infinitives of result. My conclusion points again to the importance of argument structure in an analysis of infinitives of result in particular and of modification in general.